2011
DOI: 10.1111/j.1530-0277.2011.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Smoking, and Drug Use Among Inuit Women of Childbearing Age During Pregnancy and the Risk to Children

Abstract: Background-Alcohol consumption during pregnancy, a known teratogen often associated with drug use and smoking, is a well-known public health concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 40 publications
2
46
2
8
Order By: Relevance
“…For example, substance use intervention programs should have a wider focus to encompass affect and impulse management with culturally respectful strategies. The surprising association between alcohol abuse and higher education was also found in the Qanuippitaa survey and in the present cohort during the pregnancy period (Muckle et al, 2011). It may be explained by the fact that the more educated women have larger incomes, providing them easier access to alcoholic beverages that are very expensive in the North.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…For example, substance use intervention programs should have a wider focus to encompass affect and impulse management with culturally respectful strategies. The surprising association between alcohol abuse and higher education was also found in the Qanuippitaa survey and in the present cohort during the pregnancy period (Muckle et al, 2011). It may be explained by the fact that the more educated women have larger incomes, providing them easier access to alcoholic beverages that are very expensive in the North.…”
Section: Discussionmentioning
confidence: 58%
“…Half of the Inuit surveyed used marijuana in the year preceding Qanuippitaa, and 47.1% were at risk of alcohol-related problems (Muckle, Boucher, Laflamme, & Chevalier, 2007), compared with 7.8% and less than 5%, respectively, in women in the general Canadian population (Government of . Our team (Muckle et al, 2011) recently reported a high prevalence of alcohol use, smoking, and drug use during pregnancy in a sample of 248 Nunavik women from the Hudson Bay region who participated in the Environmental Contaminants and Child Development (ECCD) study. Rates of smoking, alcohol use, binge drinking, and marijuana use were 92%, 60%, 38%, and 36%, respectively.…”
Section: Socioeconomic and Psychosocial Adversity In Inuit Mothersmentioning
confidence: 99%
See 1 more Smart Citation
“…«Il importe toutefois de noter que les études sur la consommation d'alcool pendant la grossesse ont porté de façon disproportionnée sur les femmes autochtones et les régions qu'elles habitent, ce qui soulève certaines questions méthodologiques » (Tait, 2003) Peu d'études épidémiologiques ont examiné la consommation d'alcool chez les femmes autochtones au Canada. Les données qui existent sur ce sous-groupe proviennent généralement d'enquêtes nationales (Muckle, et al, 2011;Roberts & Nanson, 2000). Une de ces études démontre que les femmes autochtones sont plus susceptibles que les hommes ou les femmes allochtones de s'abstenir de boire de l'alcool.…”
Section: La Consommation D'alcool Chez Les Femmes Et Chez Les Femmes unclassified
“…Les femmes autochtones sont plus à risque parce qu'elles sont exposées à des milieux sociaux où la toxicomanie, la consommation d'alcool et la violence sont répandues (Muckle, et al, 2011;Stout, Kipling, & Stout, 2001). Initialement, la consommation d'alcool chez les Premières Nations était considérée comme une activité agréable mais dû à des facteurs historiques (colonisation), la consommation d'alcool fut adoptée comme moyen pour échapper aux changements face à l'autonomie individuelle et collective (Tait, 2003).…”
Section: -Femmes Autochtones Davantage à Risqueunclassified